Analisis Pengaruh Budaya Organisasi dan Pengendalian Internal terhadap Kinerja Pegawai - Meike Negawati Kesek; Joseph Nugraha Tangon; Sintia Nurani Korompis (Owner : Riset dan Jurnal Akuntansi, 2021)
This paper intends to ascertain whether the influence of organizational culture and internal control on employee performance. An organization can be said to be successful if it is supported by good employee performance. Organizational culture that has long been built in the organization can certainly have an influence on the behavior of employees in it. Likewise with internal control, the better the internal control function in an organization, the employee's performance will also increase in a better and maximum direction. The data used are primary data, namely by distributing questionnaires to collect data. The research sample was ASN in the Environmental Service of North Sulawesi Province. Methods of data analysis using multiple regression. The results of this study indicate that the organizational culture variable (X1) has a significance value = 0.000 <? = 0.05, so it can be concluded that organizational culture has an effect on employee performance. Furthermore, for the test results on the Internal Control variable (X2) on Employee Performance (Y) has a significance value = 0.028 <? = 0.05, which means that Internal Control also affects employee performance. Organizational culture that is not conducive will cause employee performance to decline. However, if the organization, in this case the public sector, is able to build a good organizational culture, it will be able to improve employee performance. Likewise with internal control, the better internal control within an organization, the better the employee's performance in the organization. So that when control and supervision have been carried out properly and have been implemented by employees, the employee's performance will automatically increase.